Graft copolymer, resin composition for plating, molded article, and plated processed article
By grafting and polymerizing the graft copolymer of specific monomer components in the rubbery polymer, the problem of poor plating appearance caused by tiny concave and convexity is solved, and excellent plating characteristics are achieved.
Patent Information
- Application Number
- CN202380049390.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-24
- Filing Date
- 2023-09-15
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively solve the problem of poor plating appearance caused by tiny bumps (orange peel wrinkles) generated on the vegetative embryos of molded products.
A graft copolymer is used which grafts polymerizes monomer components in a rubbery polymer, a mixture of α-methylstyrene and an aromatic vinyl compound other than α-methylstyrene, relative to the total The content of the mixture of mass is more than 60%, and the content of rubber is more than 35%.
It effectively inhibits the tiny concave and convexity generated on the vegetative embryo, obtains an excellent plating appearance, and improves the plating bond strength and hot and cold cycleability.
Smart Images

Figure BDA0005205320770000281 
Figure BDA0005205320770000291 
Figure BDA0005205320770000301
Abstract
Description
Technical Field
[0001] The present invention relates to a graft copolymer, a resin composition for plating, a molded product, and a plated product. This application claims priority based on Japanese Patent Application No. 2022-169960 filed in Japan on October 24, 2022, the contents of which are incorporated herein by reference. Background Art
[0002] Molded products made of acrylonitrile-butadiene-styrene copolymer (ABS resin) have excellent impact resistance, mechanical strength, and chemical resistance, and are therefore used in a wide range of fields such as OA (office automation) equipment, information and communication equipment, electronic and electrical equipment, home appliances, automobiles, and construction.
[0003] In addition, when molded products made of ABS resin are plated to form plated products, they have plating characteristics such as high adhesion strength of the plated film (plating adhesion strength) and excellent thermal cycling characteristics. Therefore, even in plastic plating applications, it is used in combination with many functional resins for various applications. For example, in the automotive field, due to the requirements for impact resistance, heat resistance, and moldability, it is used in combination with polycarbonate resin as PC / ABS resin.
[0004] Plating characteristics are easily affected by the characteristics of the resin composition forming the molded product and the factors of the molding conditions. Therefore, even when a resin composition containing ABS resin is used, there is a possibility that the plating appearance is poor. In the case of poor molding conditions, the appearance of the molded product is poor, and the plating appearance is poor, such as peeling and floating of the plating film, which will significantly damage the commercial value of the final product.
[0005] In Patent Document 1, in order to solve the problem of poor plating appearance caused by the poor appearance of the molded product becoming a blank, namely, dull surface and flow marks, it is proposed to use a graft copolymer obtained by adding a hard polymer having a specific reaction conversion rate and mass average molecular weight to 100 parts by mass of a rubber-containing graft copolymer.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2007-39489 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, although Patent Document 1 can solve the problem of plating appearance caused by the dark surface and wave flow marks generated on the molded product blank, it does not solve the problem of poor plating appearance caused by tiny unevenness (orange peel wrinkles) generated on the blank, and may not be sufficient.
[0011] The object of the present invention is to provide a resin composition for plating and a graft copolymer, which can suppress the occurrence of minute irregularities (orange peel wrinkles) on a blank, obtain an excellent plating appearance, and further obtain a plated product with excellent plating adhesion and thermal cycling properties.
[0012] Technical means to solve problems
[0013] The present invention has the following aspects.
[0014] [1] A graft copolymer, which is a graft copolymer (A) formed by graft-polymerizing a monomer component (a) onto a rubber polymer, wherein the monomer component (a) comprises a mixture (a1) of α-methylstyrene and an aromatic vinyl compound other than α-methylstyrene, the mixture (a1) accounts for 60% by mass or more relative to the total mass of the monomer component (a), and the rubber content in the graft copolymer (A) is 35% by mass or more relative to the total mass of the graft copolymer (A).
[0015] [2] The graft copolymer according to [1], wherein the content of α-methylstyrene in the mixture (a1) is greater than 0% by mass and less than 28.6% by mass, when the total mass of the mixture (a1) is 100% by mass.
[0016] [3] The graft copolymer according to [1] or [2], wherein the aromatic vinyl compound other than α-methylstyrene is styrene, and the content of the styrene is 62.5% by mass to 66.7% by mass relative to the total mass of the monomer component (a).
[0017] [4] A plating resin composition comprising the graft copolymer described in any one of [1] to [3], wherein the rubber content in the plating resin composition is 10% by mass to 18% by mass relative to the total mass of the plating resin composition.
[0018] [5] A molded article obtained by molding the plating resin composition described in [4].
[0019] [6] A plated product comprising a plated film on at least a portion of the surface of the molded product described in [5].
[0020] Effects of the Invention
[0021] According to the present invention, it is possible to provide a molded article, a plating resin composition, and a graft copolymer that can provide a plated product having excellent plating characteristics. DETAILED DESCRIPTION
[0022] The following definitions of terms apply throughout this specification and claims.
[0023] The "molded article" is obtained by molding the plating resin composition of the present invention.
[0024] The “plated product” is a molded product that has been subjected to a plating treatment, and has a plated film on at least a portion of the surface of the molded product.
[0025] “Excellent plating characteristics” means that the plating appearance is good, the plating adhesion strength is high, and the thermal cycle characteristics are good.
[0026] “(Meth)acrylic acid” is a general term for acrylic acid and methacrylic acid.
[0027] “(Meth)acrylate” is a general term for acrylate and methacrylate.
[0028] The term “to” indicating a numerical range means that the numerical values described before and after it are included as the lower limit and the upper limit.
[0029] [Plating resin composition]
[0030] The first aspect of the present invention contains the graft copolymer (A) of the second aspect of the present invention. The resin composition for plating may further contain other components in addition to the graft copolymer (A) as needed within a range that does not impair the effects of the present invention.
[0031] <Graft Copolymer (A)>
[0032] The graft copolymer (A) is a copolymer in which a monomer component (a) is graft-polymerized in a rubber polymer. It should be noted that in the graft copolymer (A), it is not easy to specify how the monomer component (a) is polymerized in the rubber polymer. That is, regarding the graft copolymer (A), there are cases where it is impossible or generally impractical to directly specify it by its structure or characteristics (impossible and impractical cases). Therefore, the graft copolymer (A) is more appropriately defined as "a monomer component (a) is graft-polymerized in a rubber polymer".
[0033] (Rubber polymer)
[0034] As the rubber polymer constituting the graft copolymer (A), for example, butadiene rubbers such as polybutadiene, styrene-butadiene copolymers, and acrylate-butadiene copolymers; conjugated diene rubbers such as styrene-isoprene copolymers; acrylic rubbers such as polybutyl acrylate; olefin rubbers such as ethylene-propylene copolymers; silicone rubbers such as polyorganosiloxanes, etc. It should be noted that these rubber polymers may contain unpolymerized monomers. The rubber polymer may have a composite rubber structure or a core / shell structure. As the rubber polymer, from the viewpoint of good balance between color tone and impact resistance, butadiene rubber, acrylic rubber or their composite rubber polymers are preferred.
[0035] The average particle size of the rubber polymer is preferably 0.20 μm to 0.50 μm, more preferably 0.25 μm to 0.40 μm. If the average particle size of the rubber polymer is above the above lower limit, the plating precipitation when the molded product is plated is improved. In addition, the hot and cold cycle characteristics of the plated product are further improved. If the average particle size of the rubber polymer is below the above upper limit, the plating adhesion strength of the plated product is further improved. In addition, the fluidity of the resin composition for plating is improved. The average particle size of the rubber polymer can be measured using a particle size distribution meter to measure the particle size distribution of the mass reference, and calculated from the obtained particle size distribution. The average particle size of the rubber polymer can be controlled by adjusting the polymerization conditions (temperature, time, etc.), the type of monomer and its mixing ratio when manufacturing the rubber polymer.
[0036] There is no particular restriction on the method for producing the rubber polymer, but it is preferably produced by emulsion polymerization from the viewpoint of easy control of particle size. The emulsion polymerization can be carried out by a known method, and the catalyst, emulsifier, etc. used are not particularly restricted, and various catalysts, emulsifiers, etc. can be used.
[0037] The rubber polymer may be an enlarged rubber that has been enlarged. In addition, the average particle size, distribution, etc. can be adjusted by the enlargement operation. As the enlargement method, the following methods can be cited: mechanical coagulation, chemical coagulation, and coagulation methods based on acid-containing copolymers. As the chemical coagulation method, the following methods can be cited: adding an acidic substance to the latex of the rubber polymer to make the emulsion stability unstable and coagulate to reach the target particle size. At this time, adding an alkaline substance to stabilize the latex of the rubber polymer again. As the acidic substance, acetic acid, acetic anhydride, sulfuric acid, phosphoric acid, etc. can be cited. As the alkaline substance, potassium hydroxide, sodium hydroxide, etc. can be cited. As the coagulation method based on the acid-containing copolymer, the following method can be cited: by mixing the latex of the rubber polymer and the latex of the acid-containing copolymer, the latex of the enlarged rubber is obtained. Examples of the latex of the acid group-containing copolymer include latex of an acid group-containing copolymer obtained by polymerizing monomer components in water, wherein the monomer components include: an acid group-containing monomer (for example, a carboxyl group-containing monomer such as (meth)acrylic acid), an alkyl (meth)acrylate monomer, and other monomers copolymerizable with these monomers as required.
[0038] (Monomer component (a))
[0039] The monomer component (a) constituting the graft copolymer (A) comprises a mixture (a1) of α-methylstyrene and an aromatic vinyl compound other than α-methylstyrene. The mixture (a1) preferably comprises only α-methylstyrene and an aromatic vinyl compound other than α-methylstyrene.
[0040] Furthermore, it is preferred that a vinyl cyanide compound (a2) is contained, and other vinyl compounds (a3) may be contained as necessary.
[0041] Examples of the aromatic vinyl compound other than α-methylstyrene contained in the mixture (a1) include styrene, vinyltoluenes (p-methylstyrene, etc.), halogenated styrenes (p-bromostyrene, p-chlorostyrene, etc.), p-tert-butylstyrene, dimethylstyrene, vinylnaphthalene, etc. Among them, styrene is preferred. The aromatic vinyl compound other than α-methylstyrene may be used alone or in combination of two or more.
[0042] Examples of the vinyl cyanide compound (a2) include acrylonitrile and methacrylonitrile. Among them, acrylonitrile is preferred. These vinyl cyanide compounds (a2) may be used alone or in combination of two or more.
[0043] Other vinyl compounds (a3) are vinyl compounds that can be copolymerized with a mixture (a1) of α-methylstyrene and aromatic vinyl compounds other than α-methylstyrene and a cyanide vinyl compound (a2). Examples of such vinyl compounds include alkyl methacrylates such as methyl methacrylate and ethyl methacrylate; alkyl acrylates such as methyl acrylate, ethyl acrylate, and butyl acrylate; maleimide compounds such as N-phenylmaleimide and N-cyclohexylmaleimide; unsaturated carboxylic acid compounds such as (meth)acrylic acid, itaconic acid, and fumaric acid. These other vinyl compounds (a3) may be used alone or in combination of two or more.
[0044] Regarding the ratio of each vinyl compound in the monomer component (a), it is preferred that the mixture (a1) of α-methylstyrene and aromatic vinyl compounds other than α-methylstyrene is 60% to 85% by mass, the cyanide vinyl compound (a2) is 15% to 40% by mass, and the other vinyl compound (a3) is 0% to 25% by mass, relative to the total mass of the monomer component (a). If the ratio of each compound is within the above range, the plating adhesion strength is improved.
[0045] In addition, the ratio of the aromatic vinyl compounds other than α-methylstyrene (e.g., styrene) to the total mass of the monomer component (a) is preferably 42.0% to 80.0% by mass, more preferably 50.0% to 75.0% by mass, further preferably 60.0% to 70.0% by mass, and most preferably 62.5% to 66.7% by mass, relative to the total mass of the monomer component (a).
[0046] The proportion of α-methylstyrene to the total mass of the monomer component (a) is preferably 1.0% by mass to 40.0% by mass, more preferably 1.5% by mass to 35.5% by mass, further preferably 2.0% by mass to 30.0% by mass, and most preferably 2.5% by mass to 25.0% by mass, relative to the total mass of the monomer component (a).
[0047] The ratio of α-methylstyrene in the mixture (a1) is preferably more than 0 mass % and less than 28.6 mass % relative to the total mass of the mixture (a1). When the ratio of α-methylstyrene to the total mass of the mixture (a1) is within the above range, the plating appearance is good.
[0048] The ratio of α-methylstyrene in the mixture (a1) is more preferably 3.8% by mass or more and 26.5% by mass or less relative to the total mass of the mixture (a1). Within the above range, the plating appearance is more favorable.
[0049] Furthermore, the ratio of α-methylstyrene in the mixture (a1) is more preferably 10.7 mass % or more and 21.9 mass % or less relative to the total mass of the mixture (a1). Within the above range, both the plating appearance and the plating adhesion strength are good.
[0050] (Rubber content)
[0051] In the present invention, the ratio of the rubber polymer to the total mass of the graft copolymer (A) is referred to as "the rubber content in the graft copolymer (A)".
[0052] The content of the rubber polymer is 35% by mass or more and the content of the monomer component (a) is 65% by mass or less relative to the total mass of the graft copolymer (A). If the ratio of the rubber polymer to the monomer component (a) is within the above range, the plating adhesion strength and thermal cycling characteristics of the plated product are improved.
[0053] The proportion of the rubber polymer (rubber content) is preferably 40% by mass or more, and further preferably 50% by mass or more, relative to the total mass of the graft copolymer (A). In addition, the proportion of the rubber polymer is preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less, relative to the total mass of the graft copolymer (A).
[0054] That is, the proportion of the rubber polymer is preferably 35% by mass or more and 80% by mass or less, more preferably 40% by mass to 75% by mass, and further preferably 50% by mass to 70% by mass, based on the total mass of the graft copolymer (A).
[0055] The proportion of the monomer component (a) is preferably 20% by mass or more and 65% by mass or less, more preferably 25% by mass to 60% by mass, and further preferably 30% by mass to 50% by mass, based on the total mass of the graft copolymer (A).
[0056] (Grafting rate)
[0057] As described in detail later, the plated product is obtained by plating the molded product, but for the purpose of improving the adhesion of the plating film, the molded product is usually etched before the plating. If the molded product is etched, the rubber polymer is dissolved into the etching solution, and fine holes are formed on the surface of the molded body. It is believed that the plating adhesion strength is improved because the metal enters the fine holes. Generally speaking, there is a tendency that the closer the shape of the fine holes is to a circle, the more evenly the fine holes are dispersed, and the more the plating adhesion strength and the cold and hot cycle characteristics are improved. The rubber polymer is sometimes deformed or condensed due to the shear force when the resin composition for plating is molded. If the rubber polymer is deformed, the shape of the fine holes formed by the etching treatment is also deformed. In addition, if the rubber polymer is condensed, the dispersion state of the fine holes deteriorates. There is a tendency that the higher the grafting rate of the graft copolymer (A), the less likely it is to deform and condense the rubber polymer during molding, and the more the plating adhesion strength and the cold and hot cycle characteristics of the plated product are improved.
[0058] In order to increase the grafting rate, the rubber content in the graft copolymer (A) may be reduced during the polymerization of the graft copolymer. However, there is a tendency that the lower the rubber content, the lower the impact resistance of the molded product and the lower the plating adhesion strength of the plated product.
[0059] The inventors of the present invention have conducted intensive studies and have found that, as a result of the monomer component (a) of the graft copolymer (A) of the second embodiment of the present invention containing 60% by mass or more of a mixture (a1) of α-methylstyrene and an aromatic vinyl compound other than α-methylstyrene relative to the total mass of the monomer component (a), and the rubber content in the graft copolymer (A) is 35% by mass or more relative to the total mass of the graft copolymer (A), a molded article produced from the plating resin composition of the first embodiment of the present invention containing the graft copolymer (A) exhibits good plating characteristics.
[0060] Furthermore, it has been found that extremely good plating characteristics can be obtained by making the above-mentioned monomer component (a) constituting the graft copolymer of the second embodiment of the present invention contain a vinyl cyanide compound (a2) and another vinyl compound (a3), and by making the rubber content of the graft copolymer (A) be 10% by mass to 18% by mass based on the total mass of the plating resin composition of the first embodiment of the present invention containing the graft copolymer (A).
[0061] The graft rate of the graft copolymer (A) is preferably 20% by mass to 100% by mass, more preferably 25% by mass to 95% by mass, and even more preferably 30% by mass to 90% by mass.
[0062] It should be noted that the grafting rate is a value expressed as a percentage ((Wa / Wd)×100) of the mass (Wa) of the monomer component (a) grafted onto the rubber polymer relative to the mass (Wd) of the rubber polymer. Generally speaking, it can be calculated from the acetone-insoluble component of the graft copolymer (A) obtained after the graft polymerization in the following manner. Acetone is added to the graft copolymer (A), heated at 55°C for 3 hours, and the acetone-soluble component is extracted. Then, the acetone-insoluble component is filtered and dried, the mass is measured, and the grafting rate is calculated according to the following formula (3). It should be noted that in the following formula (3), "m" is the mass (g) of the graft copolymer (A) before extraction, "n" is the mass (g) of the acetone-insoluble component, and "L" is the rubber content (mass %) of the graft copolymer (A).
[0063] Grafting rate (%) = {(nm×L) / (m×L)}×100…(3)
[0064] The grafting rate can be obtained by filtering and drying the acetone insoluble components and measuring the monomer component (a) grafted with the rubber polymer using an infrared spectrometer. As a method for obtaining the acetone insoluble components, in addition to dissolving the graft polymer (A) in acetone as described above, it can also be obtained by dissolving the plating resin composition in acetone. In the case of a polycarbonate resin, a method such as dissolving and removing with chloroform or the like is adopted. Then, the monomer component (a) grafted with the rubber polymer can be measured using an infrared spectrometer to obtain.
[0065] (Manufacturing method)
[0066] The graft copolymer (A) is obtained by polymerizing the monomer component (a) in the presence of a rubber polymer (graft polymerization). The graft copolymer (A) thus obtained has a form in which a vinyl copolymer (which is obtained by polymerizing the monomer component (a)) is grafted onto the rubber polymer. There is no particular limitation on the method for carrying out the graft polymerization, but emulsion polymerization is preferred from the perspective of being able to control the reaction so that it proceeds stably. Specifically, there are: a method in which the monomer component (a) is added to the latex of the rubber polymer at once and then polymerized; a method in which a part of the monomer component (a) is first added to the latex of the rubber polymer and the remaining part is dripped into the polymerization system while being polymerized; a method in which the whole amount of the monomer component (a) is dripped into the latex of the rubber polymer while being polymerized, etc. The polymerization of the monomer component (a) can be carried out in one stage or in two or more stages. In the case of being carried out in two or more stages, the type and composition ratio of the vinyl compound constituting the monomer component (a) in each stage can also be changed. The graft copolymer (A) obtained by emulsion polymerization is usually in the state of latex. The polymerization conditions may be, for example, 30° C. to 95° C. for 1 to 10 hours.
[0067] In emulsion polymerization, polymerization initiators, chain transfer agents (molecular weight regulators), and emulsifiers are generally used. The rubber content of the graft copolymer (A) can be adjusted by the amount of rubber polymer added (blended amount). The grafting rate can be adjusted by the amount of rubber polymer and monomer component (a) added, the amount of polymerization initiator, and the amount of emulsifier used.
[0068] Examples of the polymerization initiator include: redox initiators (combinations of organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, paramenthane hydroperoxide, and reducing agents such as sugar-containing pyrophosphate and sulfoxylate); persulfates such as potassium persulfate; peroxides such as benzoyl peroxide (BPO), azobisisobutyronitrile, lauroyl peroxide, t-butyl peroxylaurate, and t-butyl peroxymonocarbonate. The polymerization initiator may be oil-soluble or water-soluble, and may be used in combination. These polymerization initiators may be used alone or in combination of two or more. The polymerization initiator may be added to the latex of the rubber polymer at one time or continuously. The amount of the polymerization initiator used is preferably 0.05 to 0.25 parts by mass, and more preferably 0.08 to 0.2 parts by mass, relative to 100 parts by mass of the total of the rubber polymer and the monomer component (a).
[0069] As chain transfer agents, for example, thiols such as octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, n-hexamethyl mercaptan, n-tetradecyl mercaptan, and tert-tetradecyl mercaptan; terpinolene; dimer of α-methylstyrene, etc. These chain transfer agents can be used alone or in combination of two or more. The chain transfer agent can be added to the latex of the rubber polymer at one time or continuously. The amount of the chain transfer agent used is preferably 0.1 to 0.3 parts by mass, and more preferably 0.1 to 0.2 parts by mass, relative to 100 parts by mass of the total of the rubber polymer and the monomer component (a).
[0070] Examples of the emulsifier include sodium sarcosinate, fatty acid potassium, fatty acid sodium, dipotassium alkenyl succinate, calcium rosinate, calcium abietate, carboxylates such as abietate, and alkylbenzene sulfonates. These emulsifiers may be used alone or in combination of two or more. The amount of the emulsifier used is preferably 0.1 to 0.4 parts by mass, more preferably 0.1 to 0.3 parts by mass, relative to 100 parts by mass of the total of the rubber polymer and the monomer component (a).
[0071] The graft copolymer (A) is usually obtained in the form of latex. As a method for recovering the graft copolymer (A) from the latex of the graft copolymer (A), for example, there can be mentioned: a wet method in which the latex of the graft copolymer (A) is put into hot water in which a coagulant is dissolved to coagulate in a slurry state; a spray drying method in which the latex of the graft copolymer (A) is sprayed in a heated atmosphere to semi-directly recover the graft copolymer (A), etc. As the coagulant used in the wet method, for example, there can be mentioned: inorganic acids such as sulfuric acid, hydrochloric acid, phosphoric acid, and nitric acid; metal salts such as calcium chloride, calcium acetate, and aluminum sulfate, etc., which can be selected according to the emulsifier used in the polymerization. For example, in the case of using only carboxylate as an emulsifier, one or more of the above-mentioned coagulants can be used. In the case of using an emulsifier that shows a stable emulsifying power even in an acidic region such as sodium alkylbenzene sulfonate as an emulsifier, as a coagulant, a metal salt is preferably used.
[0072] If a wet method is used, a slurry-like graft copolymer (A) can be obtained. As a method for obtaining a dry graft copolymer (A) from the slurry-like graft copolymer (A), there can be listed: first, the residual emulsifier residue is dissolved into water for washing, and then the slurry is dehydrated by a centrifugal or pressure dehydrator, and then dried with an air flow dryer, etc.; a method of simultaneously dehydrating and drying with a press dehydrator, an extruder, etc. By the above method, a powder or granular dry graft copolymer (A) can be obtained. There is no particular restriction on the washing conditions, but it is preferably washed under conditions that make the amount of emulsifier residue contained in 100% by mass of the dried graft copolymer (A) become less than 2% by mass. It should be noted that the graft copolymer (A) discharged from the press dehydrator and the extruder can also be directly sent to the extruder and the molding machine for manufacturing the resin composition without recovering it to make a molded product.
[0073] <Other thermoplastic resins>
[0074] The resin composition for plating of the present invention may be used in combination with other thermoplastic resins as needed within a range not impairing the effects of the present invention.
[0075] There are no particular restrictions on other thermoplastic resins, and examples thereof include styrene copolymers, polycarbonate resins, polyester resins, polymethyl methacrylate, polyvinyl chloride, polyethylene, polypropylene and other polyolefins, various olefin elastomers, polyacetal resins, modified polyphenylene ether (modified PPE resin), ethylene-vinyl acetate copolymers, PPS resins, PES resins, PEEK resins and polyamide resins (nylon).
[0076] Among them, styrene copolymers, polycarbonate resins, polyester resins, polymethyl methacrylate, polyvinyl chloride, modified polyphenylene ether (modified PPE resin), and polyamide resins are preferred because the effects of the present invention can be fully exhibited.
[0077] (Styrene copolymer (C))
[0078] The styrene-based copolymer (C) is a copolymer obtained by copolymerizing an aromatic vinyl compound (c1), a cyanide vinyl compound (c2), and, if necessary, other monovinyl compounds (c3). That is, the styrene-based copolymer (C) is a copolymer having monomer units derived from an aromatic vinyl compound (c1), monomer units derived from a cyanide vinyl compound (c2), and, if necessary, monomer units derived from other monovinyl compounds (c3).
[0079] The styrene-based copolymer may be used alone or in combination of two or more.
[0080] Regarding the aromatic vinyl compound (c1), the cyanide vinyl compound (c2) and other vinyl compounds (c3) used as needed in the styrene-based copolymer (C), the same compounds as the mixture (a1) of α-methylstyrene and an aromatic vinyl compound other than α-methylstyrene, the cyanide vinyl compound (a2) and other vinyl compounds (a3) previously exemplified in the description of the graft copolymer (A) can be used, and the preferred embodiments are the same.
[0081] The content of the monomer unit derived from the aromatic vinyl compound (c1) in the styrene copolymer (C) is not particularly limited, and for example, it is preferably 50% to 85% by mass relative to the total mass of the styrene copolymer (C). The content of the monomer unit derived from the cyanide vinyl compound (c2) in the styrene copolymer (C) is not particularly limited, and for example, it is preferably 15% to 50% by mass relative to the total mass of the styrene copolymer (C). The content of the monomer unit derived from the other vinyl compound (c3) in the styrene copolymer (C) is not particularly limited, and for example, it is preferably 0% to 35% by mass relative to the total mass of the styrene copolymer (C). Here, it is preferred that the total of components (c1) to (c3) is the total mass of the styrene copolymer (C).
[0082] The mass average molecular weight of the styrene copolymer (C) is, for example, preferably 50,000 to 270,000. The mass average molecular weight of the styrene copolymer (C) is a value measured using gel permeation chromatography (GPC) and converted into standard polystyrene.
[0083] The styrene copolymer (C) can be produced by copolymerizing an aromatic vinyl compound (c1), a cyanide vinyl compound (c2) and, if necessary, other vinyl compounds (c3). As the polymerization method, any known polymerization method such as emulsion polymerization, suspension polymerization, bulk polymerization or a method of combining them can be applied.
[0084] Examples of the styrene-based copolymer (C) include acrylonitrile-styrene copolymers (AS resins), styrene-acrylonitrile-N-substituted maleimide terpolymers, styrene-maleic anhydride-N-substituted maleimide terpolymers, styrene-butadiene-styrene (SBS), styrene-butadiene (SBR), hydrogenated SBS, styrene-isoprene-styrene (SIS) and other styrene-based elastomers, polystyrene, methyl methacrylate-styrene copolymers (MS resins), acrylonitrile-styrene-methyl methacrylate copolymers, and the like.
[0085] As more preferable styrene-based copolymer (C), acrylonitrile-styrene copolymer (AS resin), styrene-acrylonitrile-N-substituted maleimide terpolymer, and styrene-maleic anhydride-N-substituted maleimide terpolymer are mentioned.
[0086] (Polycarbonate resin (P))
[0087] The polycarbonate resin (P) is a resin having a carbonate bond in the main chain. The polycarbonate resin (P) is not particularly limited, and examples thereof include aromatic polycarbonate resins, aliphatic polycarbonate resins, aliphatic-aromatic polycarbonate resins, and aromatic polyester carbonate resins. The ends of these polycarbonate resins (P) may be modified to R-CO-groups or R'-O-CO-groups (R and R' both represent organic groups).
[0088] As a polycarbonate resin (P), from the viewpoint of improving the impact resistance and heat resistance of the molded article, it is preferably at least one selected from the group consisting of an aromatic polycarbonate resin and an aromatic polyester carbonate resin, and from the viewpoint of further improving the impact resistance, an aromatic polycarbonate resin is more preferably used. An aromatic polycarbonate resin is a polymer having a structural unit represented by the general formula -(-O-X1-OC(=O)-)-. X1 in the above general formula is a hydrocarbon group having one or more aromatic rings, or a group in which a heteroatom or a hetero bond (hetero bond) is introduced into the above hydrocarbon group. In X1, the atom directly bonded to the oxygen atom adjacent to X1 is a carbon atom constituting an aromatic ring. Examples of the aromatic polycarbonate resin include: a reaction product obtained by an ester exchange reaction between an aromatic dihydroxy compound and a carbonic acid diester, a polycondensate obtained by an interfacial polycondensation method between an aromatic dihydroxy compound and phosgene, and a polycondensate obtained by a pyridine method between an aromatic dihydroxy compound and phosgene.
[0089] The aromatic dihydroxy compound may be a compound having two hydroxyl groups bonded to an aromatic ring in the molecule, and examples thereof include dihydroxybenzenes such as hydroquinone and resorcinol, 4,4′-biphenol, 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as “bisphenol A”), 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl-3-methylphenyl)propane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(p-hydroxyphenyl)ethane, 2,2-bis(p-hydroxyphenyl)butane, 2,2-bis(p-hydroxyphenyl)pentane, 1,1-bis(p-hydroxyphenyl)pentane, and 1,1-bis(p-hydroxyphenyl)propane. The aromatic dihydroxy compounds include bis(p-hydroxyphenyl)-1-phenylethane, 9,9-bis(p-hydroxyphenyl)fluorene, 9,9-bis(p-hydroxy-3-methylphenyl)fluorene, 4,4'-(p-phenylene diisopropylidene)bisphenol, 4,4'-(m-phenylene diisopropylidene)bisphenol, bis(p-hydroxyphenyl) oxide, bis(p-hydroxyphenyl) ketone, bis(p-hydroxyphenyl) ether, bis(p-hydroxyphenyl) ester, bis(p-hydroxyphenyl) sulfide, bis(p-hydroxy-3-methylphenyl) sulfide, bis(p-hydroxyphenyl) sulfone, bis(3,5-dibromo-4-hydroxyphenyl) sulfone, and bis(p-hydroxyphenyl) sulfoxide. These aromatic dihydroxy compounds may be used alone or in combination of two or more.
[0090] As an aromatic dihydroxy compound, a compound having a hydrocarbon group between two benzene rings is preferred. In this compound, as a hydrocarbon group, for example, an alkylene group can be cited. The hydrocarbon group can be a hydrocarbon group substituted with a halogen. The benzene ring can be a benzene ring after the hydrogen atom contained in the benzene ring is substituted with a halogen atom. As a compound having a hydrocarbon group between two benzene rings, bisphenol A, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl-3-methylphenyl)propane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(p-hydroxyphenyl)ethane, 2,2-bis(p-hydroxyphenyl)butane, etc. can be cited. Among them, bisphenol A is preferred. These compounds having a hydrocarbon group between two benzene rings can be used alone or in combination of two or more.
[0091] Examples of the carbonic acid diester used for obtaining the aromatic polycarbonate by transesterification include dimethyl carbonate, diethyl carbonate, di-tert-butyl carbonate, diphenyl carbonate, ditolyl carbonate, etc. These carbonic acid diesters may be used alone or in combination of two or more.
[0092] The polycarbonate resin (P) may be used alone or in combination of two or more. For example, two or more polycarbonate resins having different viscosity average molecular weights may be used in combination. The molecular weight of the polycarbonate resin (P) is arbitrary and not particularly limited, but the viscosity average molecular weight (Mv) calculated from the solution viscosity is generally preferably 15,000 to 40,000, more preferably 17,000 to 30,000, and particularly preferably 18,000 to 28,000. If the viscosity average molecular weight is above the above lower limit, the impact resistance of the molded article is improved. If the viscosity average molecular weight is below the above upper limit, the fluidity of the resin composition for plating is improved.
[0093] The viscosity average molecular weight (Mv) of the polycarbonate resin (P) is a value measured by a solution viscosity method. Specifically, using a solution (sample) prepared by dissolving 0.7 g of the polycarbonate resin (P) in 100 mL of dichloromethane and an Ubellohde viscometer, the intrinsic viscosity [η] (unit: dl / g) at a temperature of 25°C is determined, and the viscosity average molecular weight (Mv) is determined according to the following formula (4).
[0094] [η] = 1.23 × 10 -4 ×Mv 0.83 …(4)
[0095] (Polyester resin (E))
[0096] Preferred polyester resins (E) include polyethylene terephthalate (PET resin), polybutylene terephthalate, polytetramethylene terephthalate, polybutylene naphthalate, various polyester elastomers, polyarylate, liquid crystal polyester resins, etc. These polyester resins may be used alone or in combination of two or more.
[0097] In addition, the PET resin used more preferably is a PET resin obtained by solid phase polymerization of a recycled and / or regranulated PET resin. Specifically, it includes: a PET resin obtained by solid phase polymerization of a recycled PET resin, a regranulated PET resin, a recycled and regranulated PET resin, etc.
[0098] Recycled PET resin is a PET resin obtained by recycling and regenerating PET resin products obtained through the molding process of PET resin. As PET resin products, representative products such as used PET bottles and food trays may be used, but they are not limited thereto, and defective PET resin products, waste generated in the molding process, etc. may also be used as objects. Therefore, by using recycled and / or regranulated PET resin, resources can be effectively utilized.
[0099] Recycled materials obtained by recycling used PET bottles, food trays, etc. need to be sorted to avoid mixing different types of materials and metals. In addition, when washing with alkaline water, etc., it is necessary to thoroughly wash with water and then dry it so that no alkaline components that promote the hydrolysis of PET resin remain.
[0100] The shape of the recycled PET resin is usually a flake shape, and the average particle size is preferably 2 mm to 5 mm. In addition, in order to remove foreign matter, a resin that has been granulated (regranulated) once may be used.
[0101] Examples of the re-granulated PET resin include a resin obtained by granulating the above-mentioned recycled PET resin, a resin obtained by granulating a commercially available pelletized product (raw material), etc. Granulation can be performed using an extruder or the like.
[0102] The PET resin may be used alone or in combination of two or more.
[0103] The other thermoplastic resin groups may be used alone or in combination of two or more.
[0104] Examples include a styrene copolymer (C) comprising an acrylonitrile-styrene copolymer (AS resin) and a styrene-acrylonitrile-N-substituted maleimide terpolymer, a combination of a styrene copolymer (C) and a polycarbonate resin (P), and a combination of a styrene copolymer (C), a polycarbonate resin (P), and a polyester resin (E).
[0105] When the other thermoplastic resin is a combination of a styrene-based copolymer (C) and a polycarbonate resin (P), it preferably contains 1 mass % to 55 mass %, 5 mass % to 52 mass %, or 6 mass % to 50 mass % of the styrene-based copolymer resin (C) and 45 mass % to 99 mass %, 48 mass % to 95 mass %, or 50 mass % to 94 mass % of the polycarbonate resin (P) (here, the total amount of the styrene-based polymer (C) and the polycarbonate resin (P) is 100 mass %).
[0106] When the other thermoplastic resin is a combination of a styrene copolymer (C), a polycarbonate resin (P) and a polyester resin (E), it preferably contains 1 mass % to 55 mass %, 5 mass % to 52 mass %, or 6 mass % to 50 mass % of the styrene copolymer (C), 30 mass % to 98 mass %, 38 mass % to 94 mass %, or 43 mass % to 93 mass % of the polycarbonate resin (P), and 1 mass % to 15 mass %, 1 mass % to 10 mass %, or 1 mass % to 7 mass % of the polyester resin (E) (here, the total amount of the styrene copolymer (C), the polycarbonate resin (P) and the polyester resin (E) is 100 mass %).
[0107] When the content of each component is within the above range, the moldability, mechanical strength, and plating properties of the reinforcing resin composition for a plating substrate will be more well-balanced.
[0108] <Other ingredients>
[0109] As other components, various additives, other resins, etc. can be listed. As additives, for example, known antioxidants, light stabilizers, ultraviolet absorbers, lubricants, plasticizers, stabilizers, transesterification inhibitors, hydrolysis inhibitors, mold release agents, antistatic agents, colorants (pigments, dyes, etc.), fillers (carbon fiber, glass fiber, wollastonite, calcium carbonate, silicon dioxide, talc, etc.), flame retardants (bromine flame retardants, phosphorus flame retardants, etc.), flame retardant aids (antimony trioxide, etc.), drip-proof agents (fluororesins, etc.), antibacterial agents, mildew inhibitors, silicone oils, coupling agents, etc. can be listed. These additives can be used alone or in combination of two or more.
[0110] It should be noted that as for the essential components and optional components used in the present invention, products recovered from polymerization steps, processing steps, molding steps, etc., or recycled products recovered from the market may be used as long as there is no problem with the quality.
[0111] <Content of each ingredient>
[0112] The content of the graft copolymer (A) is preferably 10% to 50% by mass, more preferably 15% to 40% by mass, relative to the total mass of the resin composition for plating. If the content of the graft copolymer (A) is above the above lower limit, the fluidity of the resin composition for plating is improved. In addition, the impact resistance of the molded product is improved. If the content of the graft copolymer (A) is below the above upper limit, the plating precipitation is improved.
[0113] The content of other components is preferably 0 to 60 mass %, more preferably 0 to 10 mass %, and further preferably 0 to 2 mass %, relative to the total mass (100 mass %) of the plating resin composition.
[0114] The content of the main resin component relative to the total mass (100 mass%) of the plating resin composition of the first embodiment is 60 mass% or more, preferably 70 mass% or more, more preferably 90 mass% or more, further preferably 95 mass% or more, and may be 100 mass%.
[0115] When the above-mentioned resin main component is formed by a graft copolymer (A) and a styrene copolymer (C), the content of the styrene copolymer (C) is preferably 60 to 90 parts by mass, more preferably 65 to 85 parts by mass, and further preferably 70 to 80 parts by mass, relative to 25 parts by mass of the graft copolymer (A) in the resin main component.
[0116] When the above-mentioned resin main component is formed by a graft copolymer (A), a styrene copolymer (C) and a polycarbonate resin (P), the content of the styrene copolymer (C) is preferably 1 to 45 parts by mass, and the content of the polycarbonate resin (P) is preferably 30 to 80 parts by mass, relative to 25 parts by mass of the graft copolymer (A) in the resin main component.
[0117] When the above-mentioned resin main component is formed of a graft copolymer (A), a styrene copolymer (C), a polycarbonate resin (P) and a polyester resin (E), the content of the styrene copolymer (C) is preferably 1 to 45 parts by mass, more preferably 10 to 35 parts by mass, and further preferably 15 to 25 parts by mass, relative to 25 parts by mass of the content of the graft copolymer (A) in the resin main component, the content of the polycarbonate resin (P) is preferably 30 to 80 parts by mass, more preferably 35 to 60 parts by mass, and further preferably 40 to 55 parts by mass, and the content of the polyester resin (E) is preferably 1 to 50 parts by mass, more preferably 2 to 30 parts by mass, and further preferably 3 to 10 parts by mass.
[0118] When the resin main component has the above-mentioned suitable composition, the plating characteristics (excellent appearance, plating adhesion strength, and thermal cycling resistance) of the plating resin composition are further improved.
[0119] <Rubber content>
[0120] The rubber content in the resin composition for plating is 10% to 18% by mass relative to the total mass of the resin composition for plating. If the rubber content is above the lower limit, the plating adhesion strength of the plated product is improved. If the rubber content is below the upper limit, the thermal cycle characteristics of the plated product are improved. The rubber content in the resin composition for plating can be obtained by measuring the amount of the rubber polymer used and the amount of the graft copolymer (A) based on the infrared spectrometer.
[0121] <Method for producing a resin composition for plating>
[0122] The first embodiment of the present invention is a thermoplastic resin composition for plating, which contains a graft copolymer (A), and is produced by mixing and kneading with other thermoplastic resins and other components used as needed. There is no particular limitation on the method of mixing and kneading the components, and general mixing and kneading methods can be used, such as a method of kneading with an extruder, a Banbury mixer, a kneading roll, etc. and then cutting and granulating with a granulator, etc. The thermoplastic resin composition for plating of the present invention can be molded into a molded product.
[0123] [Molding products]
[0124] The molded article is made of the above-mentioned resin composition for plating of the present invention. The molded article is obtained by molding the resin composition for plating of the present invention. As its molding method, for example, injection molding, extrusion molding, compression molding, insert molding, vacuum molding, blow molding, etc. can be cited.
[0125] Since the molded product uses the resin composition for plating of the present invention, it has excellent molded appearance and excellent plating properties. That is, when the plating treatment is implemented, it shows excellent plating adhesion strength, and the plating appearance is not easy to change during the hot and cold cycle, and the plating appearance is also excellent.
[0126] [Plating products]
[0127] The plated product comprises the above-mentioned molded product and a plated film formed on at least a portion of the surface of the molded product. The plated product is obtained by subjecting the molded product to a plating treatment. The plating treatment method is not particularly limited, and examples thereof include electroless plating methods, direct plating methods, and non-chrome plating methods. In addition, it is preferred that an etching treatment is performed using an etching solution such as a permanganate solution or a chromic acid solution before the plating treatment.
[0128] The plated product is a product in which a plated film is formed by plating at least a portion of the surface of a molded product molded by molding the resin composition for plating of the present invention, so the molded product and the plated film have excellent adhesion strength and thermal cycling properties. In addition, the blank of the molded product molded by molding the resin composition for plating of the present invention has no micro-concavities and convexities, so the plating appearance is also excellent.
[0129] The plated products can be suitably used in various applications including OA (office automation) equipment, information and communication equipment, electronic and electrical equipment, home appliances, automobiles, and buildings.
[0130] Example
[0131] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. Various determination and evaluation methods in the following examples and comparative examples are as follows. It should be noted that, in the following description, unless otherwise specified, "parts" refer to parts by mass, and "%" refers to mass %.
[0132] [Measurement and evaluation methods]
[0133] <Mass Particle Size Distribution of Rubber Polymer>
[0134] The water-diluted solution of the latex of the rubber polymer was measured for mass-based particle size distribution using a nanoparticle size distribution analyzer (manufactured by Nikkiso Co., Ltd., "Nanotrac UPA-EX150") based on the dynamic scattering theory, and the mass average particle size (μm) was calculated from the obtained particle size distribution.
[0135] <Measurement of Mass Average Molecular Weight (Mw) of Styrene Copolymer (C)>
[0136] The measurement was performed using a GPC apparatus (manufactured by Tosoh Corporation) using a solution obtained by dissolving the styrene-based copolymer (C) in tetrahydrofuran as a measurement sample, and the calculation was performed by a standard polystyrene conversion method.
[0137] <Evaluation of Plating Appearance>
[0138] The pellets of the resin composition for plating were injection molded using an 80-ton injection molding machine (manufactured by Nippon Steel Works, Ltd., "J80ADS-110U") to obtain test pieces (length 100 mm × width 100 mm × thickness 3 mm). Injection molding was performed under the conditions of a cylinder temperature of 250°C, a mold temperature of 60°C, and an injection speed of 50 mm / sec. The obtained test pieces were plated, and the appearance of the plating was visually observed and evaluated according to the following criteria.
[0139] ◎ (4 points): No minute irregularities were observed on the surface of the plated product, which was very excellent.
[0140] ○ (3 points): Some minute irregularities were observed on the surface of the plated product, which was excellent.
[0141] △ (2 points): Minor irregularities were observed on the surface of the plated product, and the plated product was judged to be at a practical level.
[0142] × (1 point): Many minute irregularities were observed on the surface of the plated product, and the plated product was not at a practical level.
[0143] (Plating A)
[0144] In the evaluation of the plating appearance, the plating process is carried out in the following order (1) to (17). (1) Degreasing → (2) Water washing → (3) Etching → (4) Water washing → (5) Acid treatment → (6) Water washing → (7) Catalytic treatment → (8) Water washing → (9) Activation treatment → (10) Water washing → (11) Chemical Ni plating → (12) Water washing → (13) Electrolytic copper plating → (14) Water washing → (15) Electrolytic Ni plating → (16) Water washing → (17) Electrolytic Cr plating
[0145] ·Conditions in each process
[0146] (1) Degreasing: The sample was treated at 50° C. for 5 minutes using CRP Cleaner (manufactured by Okuno Chemical Industries, Ltd.).
[0147] (2) Water washing: Water washing was performed at 20° C. It should be noted that water washing after (4) was also performed under the same conditions as (2).
[0148] (3) Etching: Etching treatment was performed using a mixed solution of 400 g / L of anhydrous chromic acid and 200 mL / L of sulfuric acid as an etching solution. The immersion conditions were set to 68° C.×20 minutes.
[0149] (5) Acid treatment: Immerse in 100 mL of 35% hydrochloric acid at 23°C for 1 minute.
[0150] (7) Catalytic treatment: Immerse in a mixed solution of 40 mL / L of CRP catalyst and 250 mL / L of 35% hydrochloric acid (Pd-Sn colloidal catalyst) at 30°C for 3 minutes.
[0151] (9) Activation treatment: Immerse in 100 mL of sulfuric acid at 40°C for 3 minutes.
[0152] (11) Chemical Ni plating: Immerse in a mixed solution of 160 mL / L of chemical nickel A (manufactured by Okuno Chemical Industries, Ltd.) and 160 mL / L of chemical nickel B (manufactured by Okuno Chemical Industries, Ltd.) at 35°C for 5 minutes to form a chemical plating film with a film thickness of 0.5 μm.
[0153] (13) Electrolytic copper plating: at 20°C, current density 3A / dm 2 The sample was immersed in a mixed solution of 200 g / L copper sulfate, 30 mL / L sulfuric acid and a brightener for 20 minutes to form a copper-plated film with a thickness of 20 μm.
[0154] (15) Electrolytic Ni plating: at 55°C, current density 3A / dm 2 The sample was immersed in a mixed solution of 200 g / L nickel sulfate, 45 g / L nickel chloride, 45 g / L boric acid and a brightener for 15 minutes to form a nickel-plated film with a thickness of 10 μm.
[0155] (17) Cr electroplating: at 45°C, current density 15A / dm 2 The sample was immersed in a mixed solution of 200 g / L anhydrous chromic acid and 1.5 g / L sulfuric acid for 2 minutes to form a chromium-plated film with a thickness of 0.3 μm.
[0156] <Evaluation of Plating Adhesion Strength>
[0157] The pellets of the resin composition for plating were injection molded using an 80-ton injection molding machine (manufactured by Nippon Steel Works, Ltd., "J80ADS-110U") to obtain test pieces (length 90 mm × width 50 mm × thickness 3 mm). Injection molding was performed under the conditions of a molding temperature of 250°C, a mold temperature of 60°C, and an injection speed of 5 mm / sec. The obtained test piece was plated in the following manner, and the plating film was peeled off in the vertical direction on a load measuring instrument to measure its strength, and the plating adhesion strength was determined according to the following criteria.
[0158] ◎ (4 points): The plating adhesion strength is 15 N / cm or more, which is very excellent.
[0159] ○ (3 points): The plating adhesion strength is 12 N / cm or more and less than 15 N / cm, which is excellent.
[0160] △ (2 points): The plating adhesion strength is 8 N / cm or more and less than 12 N / cm, which is not a problem in practical use.
[0161] ×(1 point): Plating adhesion strength is less than 8N / c m, or the plating film was not deposited on the entire surface of the test piece (cannot be evaluated), which did not reach a practical level.
[0162] (Plating process B)
[0163] In the evaluation of the plating adhesion strength, the plating process is carried out in the following order (1) to (15). (1) Degreasing → (2) Water washing → (3) Etching → (4) Water washing → (5) Acid treatment → (6) Water washing → (7) Catalytic treatment → (8) Water washing → (9) Activation treatment → (10) Water washing → (11) Chemical Ni plating → (12) Water washing → (13) Electrolytic copper plating → (14) Water washing → (15) Drying
[0164] ·Conditions in each process
[0165] (1) Degreasing: Treatment was performed at 50° C. for 5 minutes using a 50 mL / L solution of CRP Cleaner (manufactured by Okuno Chemical Industries, Ltd.).
[0166] (2) Water washing: Water washing was performed at 20° C. It should be noted that water washing after (4) was also performed under the same conditions as (2).
[0167] (3) Etching: Etching treatment was performed using a mixed solution of 400 g / L of anhydrous chromic acid and 200 mL / L of sulfuric acid as an etching solution. The immersion conditions were set to 68° C.×15 minutes.
[0168] (5) Acid treatment: Immerse in 100 mL of 35% hydrochloric acid at 23°C for 1 minute.
[0169] (7) Catalytic treatment: Immerse in a mixed solution of 40 mL / L of CRP catalyst and 250 mL / L of 35% hydrochloric acid (Pd-Sn colloidal catalyst) at 30°C for 3 minutes.
[0170] (9) Activation treatment: Immerse in 100 mL of sulfuric acid at 40°C for 3 minutes.
[0171] (11) Chemical Ni plating: Immerse in a mixed solution of 160 mL / L of chemical nickel A (manufactured by Okuno Chemical Industries, Ltd.) and 160 mL / L of chemical nickel B (manufactured by Okuno Chemical Industries, Ltd.) at 35°C for 5 minutes to form a chemical plating film with a film thickness of 0.5 μm.
[0172] (13) Electrolytic copper plating: at 20°C, current density 3A / dm 2 The sample was immersed in a mixed solution of 200 g / L copper sulfate, 30 mL / L sulfuric acid and a brightener for 60 minutes to form a copper-plated film with a thickness of 35 μm.
[0173] (15) Drying: Dry at 80°C for 2 hours.
[0174] <Evaluation of thermal cycle characteristics>
[0175] The pellets of the plating resin composition were injection molded using an 80-ton injection molding machine (manufactured by Nippon Steel Works, Ltd., "J80ADS-110U") to obtain test pieces (length 100 mm×width 100 mm×thickness 3 mm). The cylinder temperature was 250°C, the mold temperature was 60°C, and the injection speed was 50 mm / s. sec The obtained test piece was subjected to injection molding under the following conditions. The plated test piece was plated in the following manner, and 10 cycles were performed with "cooling at -35°C for 1 hour and heating at 90°C for 1 hour" as one cycle. After that, the state of the plated film of the plated product was visually observed, and the cold and hot cycle characteristics were determined according to the following criteria.
[0176] o (3 points): There is no morphological change such as plating expansion or peeling on the effective surface of the plated product, which is excellent.
[0177] Δ (2 points): There are slight morphological changes such as expansion and peeling on the effective surface of the plated product, but there is no problem in practical use.
[0178] × (1 point): The effective surface of the plated product has morphological changes such as plating expansion and peeling, or the plating film is not deposited on the entire surface of the test piece (cannot be evaluated), which does not meet the practical level.
[0179] (Plating process)
[0180] The plated product in the evaluation of the thermal cycle characteristics was subjected to a plating treatment in the same procedure as the above-mentioned plating process B to obtain a plated product.
[0181] <Comprehensive judgment>
[0182] In the above evaluation results, a total score of 12 to 20 points was judged as "o" excellent in the comprehensive judgment, and a total score of 11 points or less or any evaluation result with 1 point was judged as "Δ" poor in the comprehensive judgment.
[0183] [Production of Graft Copolymer (A)]
[0184] <Synthesis Example 1: Production of Rubber Polymer (g-1)>
[0185] 150 parts of water, 3.3 parts of potassium salt of tallow fatty acid, 0.14 parts of potassium hydroxide, 0.3 parts of sodium pyrophosphate, 0.20 parts of tert-dodecyl mercaptan were added to the reactor, followed by 100 parts of 1,3-butadiene, and the temperature was raised to 62°C. Next, 0.12 parts of potassium persulfate were injected to initiate polymerization. The reaction was carried out for 10 hours and reached 75°C. After further reacting at 75°C for 1 hour, 0.08 parts of sodium formaldehydesulfoxylate were injected. After removing the remaining 1,3-butadiene, the polymer was taken out to obtain a latex of a rubber polymer. The mass average particle size of the obtained rubber polymer was 0.08μm. 100 parts of a latex of a rubber polymer calculated on a solid content basis and 0.15 parts of sodium dodecylbenzenesulfonate were added to the reactor, and water was added to adjust the solid content to 36.5%. After the temperature was raised to 30°C, 1.3 parts of acetic acid was added, followed by stirring for 10 minutes and neutralization with potassium hydroxide to obtain a latex of a rubber polymer (g-1). The mass average particle size of the obtained rubber polymer (g-1) was 0.30 μm.
[0186] <Synthesis Example 2: Graft Copolymer (A-1)>
[0187] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 60 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 10 parts of acrylonitrile, 25 parts of styrene, 5 parts of α-methylstyrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to carry out polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Next, the coagulated product was centrifuged with a filter cloth, and the wet powdered graft copolymer was dried to obtain a graft copolymer (A-1).
[0188] <Synthesis Example 3: Graft Copolymer (A-2)>
[0189] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 60 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 12 parts of acrylonitrile, 25 parts of styrene, 3 parts of α-methylstyrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to perform polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Then, the coagulated product was centrifuged with a filter cloth, and the wet powder graft copolymer was dried to obtain a graft copolymer (A-2).
[0190] <Synthesis Example 4: Graft Copolymer (A-3)>
[0191] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 60 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 8 parts of acrylonitrile, 25 parts of styrene, 7 parts of α-methylstyrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to perform polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Then, the coagulated product was centrifuged with a filter cloth, and the wet powdered graft copolymer was dried to obtain a graft copolymer (A-3).
[0192] <Synthesis Example 5: Graft Copolymer (A-4)>
[0193] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 60 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 14 parts of acrylonitrile, 25 parts of styrene, 1 part of α-methylstyrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to carry out polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Then, the coagulated product was centrifuged with a filter cloth, and the wet powdered graft copolymer was dried to obtain a graft copolymer (A-4).
[0194] <Synthesis Example 6: Graft Copolymer (A-5)>
[0195] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 60 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 6 parts of acrylonitrile, 25 parts of styrene, 9 parts of α-methylstyrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to perform polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Then, the coagulated product was centrifuged with a filter cloth, and the wet powder graft copolymer was dried to obtain a graft copolymer (A-5).
[0196] <Synthesis Example 7: Graft Copolymer (A-6)>
[0197] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 40 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 15 parts of acrylonitrile, 40 parts of styrene, 5 parts of α-methylstyrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to perform polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Next, the coagulated product was centrifuged with a filter cloth, and the wet powdered graft copolymer was dried to obtain a graft copolymer (A-6).
[0198] <Synthesis Example 8: Graft Copolymer (A-7)>
[0199] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 60 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 5 parts of acrylonitrile, 25 parts of styrene, 10 parts of α-methylstyrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to perform polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Next, the coagulated product was centrifuged with a filter cloth, and the wet powdered graft copolymer was dried to obtain a graft copolymer (A-7).
[0200] <Synthesis Example 9: Graft Copolymer (A-8)>
[0201] In a closed reactor equipped with a reagent injection container, a cooling tube, a nitrogen replacement device, a jacket heater and a stirring device, 180 parts of water (including water in the latex of the rubber polymer (g-1)), 60 parts of the latex of the rubber polymer (g-1) in terms of solid content, and 0.18 parts of potassium abietic acid were added, and the liquid temperature inside the reactor was raised to 55°C while nitrogen replacement was performed and maintained for 30 minutes. Then, a solution prepared by dissolving 0.15 parts of sodium pyrophosphate, 0.008 parts of ferrous sulfate heptahydrate and 0.3 parts of glucose in 8 parts of ion exchange water was added. Subsequently, a mixed solution of 10 parts of acrylonitrile, 30 parts of styrene, 0.1 parts of cumene hydroperoxide and 0.12 parts of tert-dodecyl mercaptan was added dropwise over 4.5 hours to perform polymerization. After completion of the dropwise addition, the mixture was stirred for 30 minutes while maintaining the internal temperature at 55°C, and then cooled to obtain a latex of a graft copolymer. The obtained graft copolymer latex was diluted 1.25 times with distilled water and slowly added dropwise to a 3% sulfuric acid aqueous solution at 50°C. After the entire amount was added dropwise, the temperature was raised to 90°C and maintained for 5 minutes to coagulate. Then, the coagulated product was centrifuged with a filter cloth, and the wet powdered graft copolymer was dried to obtain a graft copolymer (A-8).
[0202] [Production of Styrene Copolymer (C)]
[0203] <Synthesis Example 10: Acrylonitrile-styrene copolymer (C-1)>
[0204] The acrylonitrile-styrene copolymer (C-1) was produced by known suspension polymerization and contained 24.1 parts of acrylonitrile and 75.9 parts of styrene, and had a reduced viscosity of 0.49 dl / g as measured with an N,N-dimethylformamide solution at 25° C. The polystyrene-equivalent molecular weight Mw was 88,000.
[0205] <Synthesis Example 11: Acrylonitrile-styrene copolymer (C-2)>
[0206] The acrylonitrile-styrene copolymer (C-2) was produced by known suspension polymerization and contained 26.7 parts of acrylonitrile and 73.3 parts of styrene, and had a reduced viscosity of 0.61 dl / g as measured with an N,N-dimethylformamide solution at 25° C. The polystyrene-equivalent molecular weight Mw was 106,000.
[0207] <Synthesis Example 12: Styrene-Acrylonitrile-N-Phenylmaleimide Terpolymer (C-3)>
[0208] The styrene-acrylonitrile-N-phenylmaleimide terpolymer (C-3) was prepared by known continuous solution polymerization, comprising 17.0 parts of acrylonitrile, 55.5 parts of styrene and 28.5 parts of N-phenylmaleimide, and having a reduced viscosity of 0.67 dl / g measured with an N,N-dimethylformamide solution at 25° C. The polystyrene-equivalent molecular weight Mw was 200,000.
[0209] [Polycarbonate resin (P)]
[0210] As the polycarbonate resin (P), the following were used.
[0211] Polycarbonate resin (P-1): "Iupilon S2000F" manufactured by Mitsubishi Engineering-Plastics Corporation (viscosity average molecular weight (Mv): 22,000).
[0212] Polycarbonate resin (P-2): "Iupilon H3000F" manufactured by Mitsubishi Engineering-Plastics Corporation (viscosity average molecular weight (Mv): 18,000).
[0213] [Polyester resin (E)]
[0214] As the polyester resin (E), the following were used.
[0215] Recycled PET resin (E-1): "UK-31" manufactured by Utsumi Recycle Systems
[0216] [Examples 1 to 14, Comparative Examples 1 to 5]
[0217] The graft copolymer (A) and other thermoplastic resins are mixed in the proportions (parts by mass) shown in Tables 2 to 5 to prepare a resin composition for plating. Using a 30 mm twin-screw extruder ("TEX30α" manufactured by Nippon Steel Works, Ltd.), the obtained resin composition for plating is melt-kneaded at a temperature of 200°C, and granulated to obtain particles of the resin composition for plating. Using the plating resin composition of each example, the plating appearance, plating adhesion strength and hot and cold cycle characteristics are evaluated. Their results are shown in Tables 2 to 5. It should be noted that the blank column in the table indicates that the component is not mixed.
[0218] [Table 1]
[0219]
[0220] [ζ2]
[0221]
[0222] [ζ3]
[0223]
[0224] [ζ4]
[0225]
[0226] [Table 5]
[0227]
[0228] The content of styrene in the graft copolymers (A-1) to (A-6) according to the Examples in Table 1 relative to the total mass of the monomer component (a) is summarized as follows.
[0229] Hereinafter, "ST" means styrene, "αMS" means α-methylstyrene, "AN" means acrylonitrile, and "parts" means parts by mass.
[0230] The content of ST in the graft copolymer (A-1) was 62.5% by mass based on 40 parts of the total weight of the monomer component (a), 25 parts of ST, 5 parts of αMS, and 10 parts of AN.
[0231] The content of ST in the graft copolymer (A-2) was 62.5% by mass based on 40 parts of the total mass of the monomer component (a), 25 parts of ST, 3 parts of αMS, and 12 parts of AN.
[0232] The content of ST in the graft copolymer (A-3) was 62.5% by mass based on 40 parts of the total mass of the monomer component (a), 25 parts of ST, 7 parts of αMS and 8 parts of AN.
[0233] The content of ST in the graft copolymer (A-4) was 62.5% by mass based on 40 parts of the total weight of the monomer component (a), 25 parts of ST, 1 part of αMS, and 14 parts of AN.
[0234] The content of ST in the graft copolymer (A-5) was 62.5% by mass based on 40 parts of the total mass of the monomer component (a), 25 parts of ST, 9 parts of αMS and 6 parts of AN.
[0235] The content of ST in the graft copolymer (A-6) was 66.7% by mass based on 60 parts of the total mass of the monomer component (a), 40 parts of ST, 5 parts of αMS and 15 parts of AN.
[0236] That is, in Table 1, the content of ST in each of the graft copolymers (A-1) to (A-6) according to the Examples is in the range of 62.5% by mass to 66.7% by mass relative to the total mass of the monomer component (a).
[0237] That is, in Table 1, the content of αMS in each of the graft copolymers (A-1) to (A-6) according to the Examples is in the range of 2.5% by mass to 25.0% by mass relative to the total mass of the monomer component (a).
[0238] That is, in Table 1, the content of AN in each of the graft copolymers (A-1) to (A-6) according to the Examples is in the range of 15.0% by mass to 35.0% by mass relative to the total mass of the monomer component (a).
[0239] The plated products obtained by plating the molded products (test pieces) of the plating resin compositions of the embodiments had no poor appearance due to the tiny irregularities on the surface of the plated products, and had excellent plating appearance. In addition, the plating adhesion strength was high, the cold and hot cycle characteristics were excellent, and the plating characteristics were good.
[0240] Compared with the embodiments, in the case of Comparative Example 3 using a graft copolymer (A-7) (the content of α-methylstyrene in the mixture (a1) of αα-methylstyrene and aromatic vinyl compounds other than α-methylstyrene as the monomer component (a) of the graft copolymer (A) is too high), the plating appearance and thermal cycling characteristics are at a level that does not cause practical problems, but the plating adhesion strength is poor.
[0241] In the case of Comparative Examples 1 and 2 using the graft copolymer (A-8) (the monomer component (a) of the graft copolymer (A) does not contain α-methylstyrene), the plating appearance was poor. In Comparative Example 4, in which the rubber content in the plating resin composition was less than the prescribed amount, the plating adhesion strength was poor. In Comparative Example 5, in which the rubber content in the plating resin composition was more than the prescribed amount, good thermal cycling properties were not obtained.
[0242] Industrial Applicability
[0243] According to the present invention, a resin composition for plating that can provide a plated product having excellent plating characteristics can be provided, and the present invention is extremely important industrially.
Claims
1. A graft copolymer, which is a graft copolymer (A) obtained by graft-polymerizing a monomer component (a) onto a rubber polymer, The monomer component (a) comprises a mixture (a1) of αα-methylstyrene and an aromatic vinyl compound other than αα-methylstyrene, wherein the content of the mixture (a1) is 60% by mass or more and 85% by mass or less relative to the total mass of the monomer component (a), The rubber content in the graft copolymer (A) is 35% by mass or more relative to the total mass of the graft copolymer (A).
2. The graft copolymer according to claim 1, wherein When the total mass of the mixture (a1) is taken as 100 mass%, the content of α-methylstyrene in the mixture (a1) is more than 0 mass% and less than 28.6 mass%.
3. The graft copolymer according to claim 1, wherein The aromatic vinyl compound other than α-methylstyrene is styrene, The content of the styrene is 62.5% by mass to 66.7% by mass based on the total mass of the monomer component (a).
4. A plating resin composition comprising the graft copolymer according to any one of claims 1 to 3, The rubber content in the plating resin composition is 10% by mass to 18% by mass relative to the total mass of the plating resin composition. 5 . A molded article obtained by molding the plating resin composition according to claim 4 . 6 . A plated product comprising a plated film on at least a portion of the surface of the molded product according to claim 5 .
Citation Information
Patent Citations
Graft copolymer, thermoplastic resin composition and molded product
JP2007039489A
Optical device and imaging apparatus including the same
JP2022169960A